Mycotoxin Exposure During the First 1000 Days of Life and Its Impact on Children’s Health: A Clinical Overview - Alvito, P (2022)
The first 1000 days of life are very sensitive to any event that alters health programming, and they represent a window for intervention to improve population health. Pregnant women, fetuses, and infants are particularly vulnerable to exposure to food contaminated with mycotoxins. This review aimed to gather data from the literature on mycotoxins exposure during intrauterine life and early childhood, and associated health risks, as assessed through human biomonitoring and mycotoxins occurrence in foods, in different continents. Maternal internal exposure to aflatoxins is associated with fetal growth restriction, while exposure to fumonisins increases the risk of offspring's neural tube defects. Mycotoxin contamination of breast milk is reported worldwide, but data on adverse effects of the lactational transfer of mycotoxins on infant health are lacking. Young children are exposed to mycotoxins through contaminated infant formulas and baby foods. Both external and internal exposure to aflatoxins and fumonisins in children are reported to be associated with growth impairment. In low-income settings, where other co-factors can affect growth, this association should be interpreted with caution. Further studies on human biomonitoring of mother-infant pairs and young children are needed to guide management strategies aiming to minimize mycotoxin exposure at critical developmental stages.